A dual-network self-healing hydrogel and a preparation method thereof
Patent Information
- Application Number
- CN202611068427.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-17
- Publication Date
- 2026-10-09
AI Technical Summary
但单一组分或其简单混合物构建的水凝胶普遍存在动态响应性不足、力学性能不佳或成胶速率慢等问题,有时还需依赖生物相容性存疑的催化剂,限制了其直接作为创面敷料的应用
[0024](1)化学设计创新性高:创造性提出将席夫碱反应体系与金属配位反应体系独立预制备,先形成第一重预凝胶再原位引入第二重网络的模块化分离,顺序化构建策略,将易相互干扰的席夫碱反应与金属配位反应解耦,从源头上杜绝了副反应,确保了网络结构的规整性与性能的可预测性。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of biomedical dressing technology, specifically relating to a dual-network self-healing hydrogel and its preparation method. Background Technology
[0002] With the increasing pursuit of beauty, cosmetic medicine has become a consumer hotspot. The widespread application of minimally invasive techniques such as laser treatments, microneedling, and chemical peels, while bringing cosmetic benefits, inevitably causes varying degrees of reversible damage to the skin's epidermis, temporarily weakening the skin barrier function and potentially leading to postoperative reactions such as erythema, edema, and even pigmentation or scarring. Therefore, developing functional materials that can effectively promote wound repair after such minimally invasive procedures has become an important research topic.
[0003] Hydrogels are considered ideal candidates for wound dressings due to their three-dimensional network structure similar to the extracellular matrix, good biocompatibility, and suitable moisturizing properties. However, existing injectable hydrogels still struggle to simultaneously achieve good adhesion to wet tissue, excellent mechanical properties, and easy replacement. In particular, when attempting to construct multi-network hydrogels to comprehensively improve performance, non-specific interactions easily occur between different functional groups, leading to interference in the cross-linking process, disordered network structure, and ultimately, the overall performance of the material is far below expectations.
[0004] Polyethylene glycol (PEG) is often used as a building block in hydrogels due to its good biocompatibility and modifiability. By derivatizing the ends of PEG (e.g., modifying them with amino or carboxyl groups), it can participate in various chemical cross-linking reactions. However, hydrogels constructed from single components or simple mixtures generally suffer from insufficient dynamic responsiveness, poor mechanical properties, or slow gelation rates. They also sometimes require catalysts with questionable biocompatibility, limiting their direct application as wound dressings.
[0005] Therefore, there is an urgent need to develop a new type of smart hydrogel material that integrates rapid gelation, adaptive adhesion, and intrinsic self-healing capabilities. Furthermore, its preparation process must avoid the inherent interference of multi-component reaction systems, thereby providing an efficient, safe, and user-friendly wound dressing for non-chronic wounds such as those following minimally invasive surgery. Summary of the Invention
[0006] The primary objective of this invention is to address the shortcomings of existing technologies by providing a dual-network self-healing hydrogel with a clear network structure and excellent synergistic performance.
[0007] Another objective of this invention is to provide a method for preparing the above-mentioned hydrogel. This method employs a functional modular pretreatment and sequential cross-linking strategy, which avoids mutual interference between different cross-linking chemical reactions from the source. The process is simple and highly controllable.
[0008] Another object of the present invention is to provide the above-mentioned hydrogel as a high-performance wound dressing, particularly for use in the care of non-chronic skin wounds.
[0009] To achieve the above-mentioned technical objectives and effects, the present invention is implemented through the following technical solution:
[0010] In a first aspect of the present invention, a dual-network self-healing hydrogel is provided, comprising an interpenetrating first dynamic covalent network and a second metal coordination enhancement network, which are three-dimensional entangled structures with two interpenetrating networks and phase separation regions of less than 10 μm that cannot be observed under a scanning electron microscope.
[0011] The first dynamic covalent network is formed by cross-linking the aldehyde group of oxidized hyaluronic acid (OHA) with the amino group of bi-amino-terminated polyethylene glycol (NH2-PEG-NH2) through a Schiff base reaction;
[0012] The second heavy metal coordination enhancement network is formed by cross-linking catechol groups on sodium alginate-dopamine graft (SA-DA) with ferric ions through coordination bonds;
[0013] In some specific embodiments, the dual-network self-healing hydrogel described above has a molecular weight of 1000-10000 Da for the dual-terminated amino polyethylene glycol (NH2-PEG-NH2), preferably 2000-5000 Da.
[0014] In some specific implementations, the trivalent iron ions in the aforementioned dual-network self-healing hydrogel are selected from either ferric chloride hexahydrate or ferric sulfate hydrate, preferably ferric chloride hexahydrate.
[0015] In some specific implementations, the concentrations (w / v) of each component in the reaction system of the above-mentioned dual-network self-healing hydrogel are as follows: oxidized hyaluronic acid 1%-4%, bi-amino-terminated polyethylene glycol 0.1%-5%, sodium alginate-dopamine graft 0.5%-4%, and ferric ions (calculated as ferric chloride hexahydrate) 0.01%-0.5%.
[0016] In a second aspect of the present invention, a method for preparing a dual-network self-healing hydrogel is provided. The method employs a functional modular separation and sequential construction strategy, which involves independently pre-preparing a Schiff base reaction system and a metal coordination reaction system, first forming a first-layer pregel, and then in situ introducing a second-layer network. Specifically, the method includes the following steps:
[0017] S1. Mix the bi-amino-terminated polyethylene glycol solution with the oxidized hyaluronic acid solution to undergo a Schiff base reaction and form a first-layer network pregel.
[0018] S2. Premix the sodium alginate-dopamine graft solution with the ferric ion solution to obtain a complexation mixture;
[0019] S3. Within 5-15 seconds after the first network pregelation (before it is fully cured), add the coordination complex mixture obtained in step S2, and stir it evenly at a speed of 300-500 rpm for 30-60 seconds to make the second coordination network form in situ in the first network, thus obtaining the dual-network self-healing hydrogel.
[0020] In some specific embodiments, in the preparation method of the above-mentioned dual-network self-healing hydrogel, in step S2, the preparation method of the sodium alginate-dopamine graft (SA-DA) is as follows: sodium alginate is placed in purified water to obtain a sodium alginate aqueous solution with a concentration of 0.1%-0.5%. 1-ethyl-(3-dimethylaminopropyl)carbodiimide and N-hydroxysuccinimide are added to the sodium alginate aqueous solution. After activation for 20-45 min, dopamine hydrochloride powder is added. The pH is controlled at 4.5-6.0 throughout the reaction. After reacting in the dark for 12-18 h, it is dialyzed in purified water for 48-96 h and then freeze-dried to obtain the sodium alginate-dopamine graft (SA-DA). The dopamine substitution degree of the sodium alginate-dopamine graft is calculated to be 25%-35% by the characteristic peak area at 6.5-7.0 ppm of the proton nuclear magnetic resonance spectrum.
[0021] In some specific embodiments, the preparation method of the above-mentioned dual-network self-healing hydrogel is characterized in that the mass ratio of 1-ethyl-(3-dimethylaminopropyl)carbodiimide to sodium alginate is (0.9~1):1, the mass ratio of N-hydroxysuccinimide to sodium alginate is (0.5~1.6):1, and the mass ratio of dopamine hydrochloride to sodium alginate is (1~2):1.
[0022] In a third aspect of the invention, the use of a dual-network self-healing hydrogel in a biomedical dressing for the care of non-chronic skin wounds such as superficial wounds, small abrasions, cuts, and post-laser / photon / chemical peels / micro-plastic surgery is provided.
[0023] Compared with the prior art, the present invention has the following significant advantages:
[0024] (1) High innovation in chemical design: The innovative approach proposes to independently prepare the Schiff base reaction system and the metal coordination reaction system, first form the first layer of pregel and then introduce the second layer of network in situ, and adopt a modular separation and sequential construction strategy to decouple the Schiff base reaction and the metal coordination reaction that are prone to mutual interference, thereby eliminating side reactions from the source and ensuring the regularity of the network structure and the predictability of the performance.
[0025] (2) Excellent performance integration: Convenient injectability allows for easy application to wounds of any shape via syringe; Excellent tissue adhesion enables the dressing to form multiple strong bonds with the tissue surface, making it less prone to falling off; Rapid self-healing: Dual dynamic network ensures that the material can quickly heal itself after damage (such as microcracks), restoring integrity and function.
[0026] (3) Good biocompatibility and safety: The raw materials are natural products with good biocompatibility or approved medical materials, and the preparation process does not require the use of toxic cross-linking agents (such as glutaraldehyde).
[0027] (4) The preparation process is simple and controllable: it can be simply mixed according to the steps when used, which is very suitable for industrial production and immediate clinical application; the application prospects are broad: this hydrogel can not only be used for non-chronic wounds, but its modular design also makes it easy to expand to the field of infected wound treatment or tissue regeneration by loading drugs or cells.
[0028] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. Attached Figure Description
[0029] Figure 1 The image shown is a scanning electron microscope image of the dual-network self-healing hydrogel prepared in Example 3 of this invention. It shows that the dual-network hydrogel prepared in Example 3 has a porous three-dimensional network structure with a pore size of about 50-200 μm. The two networks are interpenetrating and there is no obvious phase separation, which confirms the formation of the interpenetrating network structure and indicates that the first and second networks interpenetrate to form a three-dimensional entangled structure.
[0030] Figure 2 The 1H NMR spectrum of the sodium alginate-dopamine graft prepared in Example 1 and sodium alginate ( 1 (H NMR), in which SA-DA showed a dopamine aromatic proton peak at 6.5-7.0 ppm, confirming the successful grafting of sodium alginate-dopamine.
[0031] Figure 3 Fourier transform infrared (FTIR) spectra of sodium alginate-dopamine grafts prepared in Example 1 and sodium alginate, wherein SA-DA are at 1520 cm⁻¹. -1 and 1091 cm -1 The presence of -C=C- aromatic ring stretching and CN-amide bond stretching peaks at the locations confirms the successful grafting of sodium alginate-dopamine.
[0032] Figure 4 The 1H NMR spectrum of oxidized hyaluronic acid and hyaluronic acid prepared in Example 2 ( 1 The H NMR spectrum showed a hemiacetal proton peak at 4.85-5.00 ppm for OHA, confirming the successful preparation of oxidized hyaluronic acid.
[0033] Figure 5 The Fourier transform infrared (FTIR) spectra of oxidized hyaluronic acid and hyaluronic acid prepared in Example 2 are shown, with OHA at 1730 cm⁻¹. -1 The presence of an absorption peak due to the bending vibration of the aldehyde group C=O confirms the successful preparation of oxidized hyaluronic acid.
[0034] Figure 6(a) , 6(b) Figures 6 and 6c show the strain amplitude scanning test results of the hydrogels prepared in Example 3, Comparative Example 1, and Comparative Example 2, respectively.
[0035] Figure 7 The image shows the alternating step strain scanning test results of the dual-network self-healing hydrogel prepared in Example 3 of this invention.
[0036] Figure 8 This is an experimental diagram illustrating the self-healing process of the dual-network self-healing hydrogel prepared in Example 3 of the present invention.
[0037] Figure 9 This is a diagram illustrating the adhesion properties of the dual-network self-healing hydrogel prepared in Example 3 of the present invention to pigskin.
[0038] Figure 10 This is a quantitative data graph showing the cell growth promotion effect of the dual-network self-healing hydrogels prepared in Example 3 and Comparative Examples 1-2 of the present invention. Detailed Implementation
[0039] To make the above-mentioned objects, features, and advantages of the present invention more apparent and understandable, the specific embodiments of the present invention will be described in detail below with reference to the embodiments. The described embodiments are only some embodiments of this application, and not all of them. The present invention is not limited to the following embodiments. Unless otherwise specified, the technical means used in the following embodiments are conventional means well known to those skilled in the art, and the materials, reagents, etc. used in the following embodiments can be obtained commercially unless otherwise specified.
[0040] Example 1
[0041] Preparation of sodium alginate-dopamine graft
[0042] Dissolve 0.5 g of sodium alginate powder in 100 mL of purified water. After the sodium alginate is completely dissolved, add 0.48 g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide (EDC) and 0.80 g of N-hydroxysuccinimide (NHS). After activation for 30 min, add 0.5 g of dopamine hydrochloride (DA·HCl). Maintain the pH between 4.5 and 6 throughout the reaction by adding 0.1 M HCl or NaOH. Then, react in the dark for 12 h. After the reaction is complete, place the product in a dialysis bag and dialyze it in purified water for three days. Finally, freeze-dry to obtain the sodium alginate-dopamine graft (SA-DA).
[0043] Figure 2 The proton NMR spectra of SA-DA and SA prepared in Example 1 ( 1 H NMR). By 1 The H NMR spectrum shows that, compared to SA, SA-DA has... 1 A novel peak was observed in the 1H NMR spectrum at 6.5–7.0 ppm, attributed to the aromatic protons of dopamine. Additionally, other typical peaks were observed between 2.8 and 3.1 ppm, likely due to the -CH2-CH2- group connecting the dopamine and amide groups located on the dopamine. 1 The H NMR spectrum showed that the degree of dopamine substitution was 30.3%.
[0044] Figure 3 The Fourier transform infrared (FTIR) spectra of the sodium alginate-dopamine graft prepared in Example 1 and sodium alginate further confirmed the structure of SA-DA. At 3400 cm⁻¹ in the SA spectrum... -1 A broad and strong band appeared at 1721 cm⁻¹, which corresponds to the stretching vibration of the -OH group. Compared to the spectrum of SA, the spectrum of SA-DA showed a stronger band at 1721 cm⁻¹. -1 An absorption peak is observed at 1520 and 1091 cm⁻¹, which is likely due to the vibrational absorption peak of -COOH. Furthermore, the SA-DA structure shows absorption peaks at 1520 and 1091 cm⁻¹, respectively. -1 The stretching of the -C=C- aromatic ring and the stretching of the CN-amide bond were verified, which confirms the successful synthesis of SA-DA.
[0045] Example 2
[0046] Preparation of oxidized hyaluronic acid
[0047] Dissolve 0.5g of hyaluronic acid powder (HA) in 100mL of purified water. Once the hyaluronic acid is completely dissolved, weigh out sodium periodate (NaIO4) powder (NaIO4 to hyaluronic acid molar ratio 1.2:1) and add it to the hyaluronic acid solution. Mix and stir for 2 hours under light-protected conditions. Then add 1.0mL of ethylene glycol and stir for 1 hour to terminate the reaction. After the reaction is complete, transfer the solution to a dialysis bag and dialyze it in purified water for three days. After dialysis, freeze-dry for two days to obtain a white, spongy solid, which is oxidized hyaluronic acid (OHA).
[0048] Figure 4 The ¹H NMR spectra of OHA and HA prepared in Example 2 are shown below. Figure 4 As can be seen, OHA exhibits a relatively small new peak at 4.85-5.00 ppm compared to HA. This corresponds to the formation of a hemiacetal proton H by the aldehyde group and the adjacent hydroxyl group, while no corresponding peak was observed in the spectrum of HA. This indicates that sodium periodate oxidizes the vicinal diol structure of HA to generate an aldehyde group, demonstrating the successful preparation of OHA.
[0049] Figure 5 Fourier transform infrared (FTIR) spectra of OHA and HA prepared in Example 2. Figure 5 HA in the middle molecule exhibits symmetric and asymmetric vibrational signals of carboxylates (1400 and 1600 cm⁻¹). -1 ), and the absorption peaks of the sugar ring backbone (1040~1100cm). -1 ); The FTIR spectrum of OHA at 1730 cm⁻¹ -1 There is a relatively weak absorption peak at this point, corresponding to the C=O bending vibration absorption peak of the aldehyde group, which indicates that the vicinal diol structure of HA was successfully oxidized to generate two aldehyde groups.
[0050] Example 3
[0051] Preparation of dual-network self-healing hydrogels
[0052] S1. Prepare a 2% bi-amino-terminated polyethylene glycol (molecular weight 2000 Da) solution and a 4% oxidized hyaluronic acid solution using purified water. Take 0.2 mL of the bi-amino-terminated polyethylene glycol solution and 1.6 mL of the oxidized hyaluronic acid solution and place them in a container. Stir with a glass rod. The solution will rapidly transform into a homogeneous, non-flowing, transparent gel within about 10 seconds, thus forming the first-layer network pregel.
[0053] S2. Prepare a 3% sodium alginate-dopamine graft solution and a 0.3% ferric chloride hexahydrate solution separately using purified water. In another container, gently mix 0.4 mL of sodium alginate-dopamine graft solution with 0.1 mL of ferric chloride hexahydrate aqueous solution. The solution will instantly darken in color, forming a complex mixture.
[0054] S3. Within 10 seconds of the formation of the first network pregel, add the coordination complex mixture obtained in step S2 to the pregel container obtained in step S1, and stir at approximately 400 rpm for about 45 seconds to ensure thorough and uniform mixing. The entire hydrogel system transforms into a uniform light brown double-network self-healing hydrogel within 1-2 minutes.
[0055] Performance Testing: A rotational rheometer was used to perform time-scan tests on the hydrogel prepared in Example 3 under alternating strain conditions. A constant frequency of 25 rad / s and a temperature of 25°C were set. First, the strain was set to 1%, and a time-scan test was performed for 180 s. Then, the strain was set to 500% (the structural failure stage), and a time-scan test was performed for 60 s. This process was repeated three times. The test completed a "failure-recovery" cycle of the hydrogel structure, and the storage modulus G′ and loss modulus G″ were recorded during the test. Rheological self-healing tests showed that in the alternating strain cycle of 1%→500%→1%, the storage modulus G′ recovered to 90% of its initial value.
[0056] Example 4
[0057] Preparation of dual-network self-healing hydrogels
[0058] S1. Prepare 0.4% diamino-terminated polyethylene glycol (molecular weight 5000 Da) solution and 4% oxidized hyaluronic acid solution separately using purified water. Take 0.5 mL of the diamino-terminated polyethylene glycol solution and 0.5 mL of the oxidized hyaluronic acid solution into a container, stir with a glass rod, and the solution will transform into a homogeneous, non-flowing transparent gel within about 15 seconds, forming the first network pregel.
[0059] S2. Prepare 2% sodium alginate-dopamine graft solution and 0.04% ferric chloride hexahydrate solution separately using purified water. In another container, gently mix 0.5 mL of sodium alginate-dopamine graft solution with 0.5 mL of ferric chloride hexahydrate aqueous solution. The solution turns very light brown, forming a complex mixture.
[0060] S3. Within 15 seconds of the formation of the first network pregel, add the coordination complex mixture obtained in step S2 to the pregel container obtained in step S1. Stir with a glass rod at approximately 300 rpm for approximately 55 seconds to ensure thorough and uniform mixing. The entire hydrogel system transforms into a uniform light brown double-network self-healing hydrogel within approximately 2 minutes.
[0061] Performance testing: The hydrogel prepared in Example 4 was tested using the same method as in Example 3. Rheological self-healing testing showed that, during alternating strain cycles of 1%→500%→1%, the storage modulus G′ recovered to 84% of its initial value, indicating good self-healing properties.
[0062] Example 5
[0063] Preparation of dual-network self-healing hydrogels
[0064] S1. Prepare 5% diamino-terminated polyethylene glycol (molecular weight 10000 Da) solution and 4% oxidized hyaluronic acid solution separately using purified water. Take 0.5 mL of the diamino-terminated polyethylene glycol solution and 0.5 mL of the oxidized hyaluronic acid solution into a container, stir with a glass rod, and the solution will rapidly transform into a homogeneous, non-flowing transparent gel within 5 seconds, forming the first network pregel.
[0065] S2. Prepare 4% sodium alginate-dopamine graft solution and 0.5% ferric chloride hexahydrate solution separately using purified water. In another container, gently mix 0.5 mL of sodium alginate-dopamine graft solution with 0.5 mL of ferric chloride hexahydrate aqueous solution. The solution instantly turns dark brown, forming a complex mixture.
[0066] S3. Within 8 seconds of the formation of the first network pregel, add the coordination complex mixture obtained in step S2 to the pregel container obtained in step S1. Stir at approximately 500 rpm for approximately 35 seconds to ensure thorough and uniform mixing. The entire hydrogel system transforms into a uniform, dark brown, double-network self-healing hydrogel within approximately 1 minute.
[0067] Performance testing: The hydrogel prepared in Example 5 was tested using the same method as in Example 3. Rheological self-healing testing showed that the storage modulus G′ recovered to 94% of its initial value during alternating strain cycles of 1%→500%→1%.
[0068] Comparative Example 1
[0069] Hydrogel containing only the first layer of network
[0070] Without adding sodium alginate-dopamine graft and ferric chloride hexahydrate, only by mixing the bi-amino-terminated polyethylene glycol solution and the oxidized hyaluronic acid solution in the proportions of Example 3, a single network hydrogel formed by Schiff base reaction was obtained.
[0071] Comparative Example 2
[0072] Hydrogels prepared by disordered mixing method
[0073] All components in Example 3 (bi-amino-terminated polyethylene glycol, oxidized hyaluronic acid, sodium alginate-dopamine graft, and ferric chloride hexahydrate) were mixed simultaneously in one step to obtain a hydrogel with a disordered cross-linked network.
[0074] Performance testing
[0075] (1) Rheological properties
[0076] The hydrogel prepared in Example 3 was tested using a rotational rheometer. The test conditions for strain scanning were: temperature 25°C, strain amplitude of 0.1% to 1000%, fixed frequency of 1 rad / s, monitoring of the linear viscoelastic region, and recording of storage modulus G′ and loss modulus G″ during the test. Figure 6(a) , 6(b) Figure 6(c) shows the strain scanning test of the hydrogels prepared in Example 3, Comparative Example 1 and Comparative Example 2 in the range of 0.1% to 1000%, with a fixed frequency of 1 rad / s. All three groups of hydrogels exhibited solid-like elastic properties (when G′>G″), and the intersection of the G′ and G″ curves at 500%, 410%, and 320% were the critical strain points of the three groups of hydrogels, respectively. This indicates that the hydrogel prepared in Example 3 has the most stable three-dimensional network structure, can adapt to wounds of different shapes, and can also provide solid protection for the wound surface.
[0077] Self-healing performance: Time-scan testing under alternating strain conditions was employed. A constant frequency of 25 rad / s and a temperature of 25℃ were set. First, the strain was set to 1%, and a time-scan test was performed for 180 s. Then, the strain was set to 500% (the structural failure stage), and a time-scan test was performed for another 60 s. This process was repeated three times. The test completed a "failure-recovery" cycle of the hydrogel structure, and the storage modulus G′ and loss modulus G″ were recorded during the test. Figure 7 The hydrogel prepared in Example 3 showed a significant decrease in G′ under a high strain of 500%, indicating that the hydrogel structure was disrupted. When the applied strain was reduced to 1%, the G′ value quickly recovered to near the initial gel state, indicating that the hydrogel underwent a rapid sol-gel transition and the structure rapidly recovered. The self-healing ability of the dual-network self-healing hydrogel is attributed to the dynamic imine bonds (-C=N-) and the interaction between catechol groups and ferric ions (Fe). 3+ Reversible coordination bonds are formed between the atoms. Therefore, hydrogels can quickly recover their original shape after being damaged by external forces.
[0078] (2) Self-healing performance
[0079] To further demonstrate the self-healing properties of the dual-network self-healing hydrogel, such as Figure 8As shown, the hydrogel prepared in Example 3 was applied to a finger and completely cut off. Then, the two fresh cut surfaces were gently brought into contact. It can be seen that the hydrogel reconnected as one, and the hydrogel did not break off when the finger was bent.
[0080] (3) Tissue adhesion performance test
[0081] The adhesion strength of the hydrogel to pigskin was evaluated using an overlap shear test. Figure 9 (a) shows that fresh pigskin was cut into standard sizes, and the hydrogel prepared in Example 3 was coated onto one piece of pigskin, and then another piece of pigskin was immediately covered on top, with a contact area of approximately 1 cm². 2 Adhesion performance was tested using a 200g weight; such as Figure 9 As shown in (b), the hydrogel prepared in Example 3 was adhered to pigskin and twisted. The hydrogel did not fall off in any of the above tests, which proves that the hydrogel has excellent tissue adhesion ability.
[0082] (4) In vitro cell proliferation assay (MTT method)
[0083] The viable cells were prepared into a single-cell suspension and their numbers were counted to achieve a cell density of 1×10⁻⁶. 4 Cells were seeded at a density of 1 / mL into 96-well plates, with 200 μL of cell suspension added to each well. The plates were divided into six groups: control group, comparative example 1, comparative example 2, example 3, example 4, and example 5. After the cells adhered, the old culture medium was removed, and new culture medium containing the sample (sample:medium medium = 1:4) was added. The control group continued to use the same culture medium. Five replicates were set for each sample from examples 3-5 and comparative examples 1-2, and the plates were incubated at 37°C with 5% CO2 for 1, 2, and 3 days. At each time point, 20 μL of MTT solution (prepared with PBS at pH 7.4) was added to the corresponding well, and the plates were incubated for another 4 hours. The plates were then quickly inverted, the supernatant was discarded, and 150 μL of dimethyl sulfoxide (DMSO) was added to each well. The plates were shaken for 10 min to dissolve the MTT crystals. The absorbance (OD) of each well at 490 nm was measured using an ELISA reader. 490 The cell viability of the experimental group was calculated using the following formula: (The formula is missing from the provided text.)
[0084] Among them, OD test The absorbance and OD of the cells processed in the sample group DMSO The absorbance of DMSO, OD control The absorbance of cells treated with culture medium.
[0085] like Figure 10As shown in the figure, the cell viability of the example group was higher than that of the comparative group, indicating that the dual-network self-healing hydrogel prepared in the example can significantly promote cell growth.
[0086] The above description is merely a preferred embodiment of the present invention and does not constitute any limitation on the present invention. Any simple modifications, alterations, or equivalent structural changes made to the above embodiments based on the technical essence of the invention shall still fall within the protection scope of the present invention.
Claims
1. A dual-network self-healing hydrogel, characterized in that, The three-dimensional entangled structure contains an interpenetrating first dynamic covalent network and a second metal coordination enhancement network, which are interpenetrating two networks and have a phase separation region of less than 10 μm that cannot be observed under a scanning electron microscope. The first dynamic covalent network is formed by cross-linking the aldehyde group of oxidized hyaluronic acid with the amino group of bi-amino polyethylene glycol through a Schiff base reaction. The second heavy metal coordination enhancement network is formed by cross-linking of catechol groups on sodium alginate-dopamine grafts with ferric ions through coordination bonds.
2. The dual-network self-healing hydrogel according to claim 1, characterized in that, The molecular weight of the double-amino-terminated polyethylene glycol is 1000-10000 Da, preferably 2000-5000 Da.
3. The dual-network self-healing hydrogel according to claim 1, characterized in that, The ferric ions are selected from either ferric chloride hexahydrate or ferric sulfate hydrate, preferably ferric chloride hexahydrate.
4. The dual-network self-healing hydrogel according to any one of claims 1-3, characterized in that, The concentrations (w / v) of each component in the reaction system are as follows: oxidized hyaluronic acid 1%-4%, bi-amino-terminated polyethylene glycol 0.1%-5%, sodium alginate-dopamine graft 0.5%-4%, and ferric ions (calculated as ferric chloride hexahydrate) 0.01%-0.5%.
5. A method for preparing a dual-network self-healing hydrogel as described in any one of claims 1-4, characterized in that, The method employs a functional modular separation and sequential construction strategy that involves independently pre-preparing the Schiff base reaction system and the metal coordination reaction system, forming a first-layer pregel, and then in situ introducing a second-layer network. Specifically, it includes the following steps: S1. Mix the bi-amino-terminated polyethylene glycol solution with the oxidized hyaluronic acid solution to undergo a Schiff base reaction and form a first-layer network pregel. S2. Premix the sodium alginate-dopamine graft solution with the ferric ion solution to obtain a complexation mixture; S3. Within 5-15 seconds after the first network pregelation (before it is fully cured), add the coordination complex mixture obtained in step S2, and stir it evenly at a speed of 300-500 rpm for 30-60 seconds to make the second coordination network form in situ in the first network, thus obtaining the dual-network self-healing hydrogel.
6. The method for preparing the dual-network self-healing hydrogel according to any one of claims 1-4, as described in claim 5, is characterized in that, In step S2, the preparation method of the sodium alginate-dopamine graft is as follows: Sodium alginate is placed in purified water to obtain a sodium alginate aqueous solution with a concentration of 0.1%-0.5%. 1-Ethyl-(3-dimethylaminopropyl)carbodiimide and N-hydroxysuccinimide are added to the sodium alginate aqueous solution. After activation for 20-45 min, dopamine hydrochloride powder is added. The pH is controlled at 4.5-6.0 throughout the reaction. After reacting in the dark for 12-18 h, the solution is dialyzed in purified water for 48-96 h and then lyophilized to obtain the sodium alginate-dopamine graft. The dopamine substitution degree of the sodium alginate-dopamine graft is calculated to be 25%-35% by the characteristic peak area at 6.5-7.0 ppm of the 1H NMR spectrum.
7. The method for preparing the dual-network self-healing hydrogel according to any one of claims 1-4, as described in claim 6, is characterized in that, The mass ratio of 1-ethyl-(3-dimethylaminopropyl)carbodiimide to sodium alginate is (0.9~1):1, the mass ratio of N-hydroxysuccinimide to sodium alginate is (0.5~1.6):1, and the mass ratio of dopamine hydrochloride to sodium alginate is (1~2):
1.
8. The use of the dual-network self-healing hydrogel according to any one of claims 1-4 in a biomedical dressing for the care of non-chronic skin wounds such as superficial wounds, small wounds, abrasions, cuts, and post-laser / photon / chemical peels / micro-plastic surgery.